Clinical use of misoprostol for cervical ripening before transcervical procedures in non pregnant women: a randomized comparison of vaginal and sublingual administrations - Udhayakumari, T.; Sasirekha, R.; Rani, P. Reddi (International Journal of Research in Medical Sciences, 2017)
Background: Endometrial sampling techniques like endometrial biopsy, Fractional curettage, Dilatation & curettage and hysteroscopy are the common gynaecological outpatient transcervical diagnostic procedures for various clinical conditions. Complications encountered during these procedures are often due to difficulties in cervical dilatation. The incidence of these complications can be reduced if cervix is ripened before the procedures. The aim of the present study was to evaluate the efficacy of 400mcg of misoprostol administered vaginally or sublingually for cervical ripening before transcervical gynaecological diagnostic procedures in both pre and post-menopausal women. Methods: Non pregnant pre and post-menopausal women scheduled for transcervical diagnostic procedures were assigned by computerized randomization to receive 400 mcg of misoprostol, administered either sublingually or vaginally 3-4 hours prior to the procedure. The primary outcome in this study was the pre procedural cervical width as measured by the largest number of Hegar dilators. The side effects related to misoprostol and complications associated with the procedure if any also noted. Results: Patients were randomized to receive sublingual (50) or vaginal (50) misoprostol. The two groups were comparable in terms of age, BMI (body mass index), parity, menopausal status and indications for diagnostic procedures. The mean cervical dilatation in sublingual group was 7.28 ± 2.21 mm and it was 6.57 ± 2.24 mm in vaginal group which was statistically similar among the groups. There were no complications associated with the procedure. Side effects were also comparable among the groups. Conclusion: Even though we found sublingual route is an effective alternate to vaginal administration of misoprostol for cervical ripening before transcervical diagnostic procedures like endometrial biopsy, fractional curettage and dilatational curettage in non pregnant pre and post-menopausal women especially when women feel uncomfortable with vaginal route. However, the optimal dose and time interval remains to be identified. It needs larger randomized control trials are required to prove clinical significance if any.